Factors Associated with Length of Stay of Inpatients: A Cross-sectional Study at RSD KRMT Wongsonegoro, Semarang, 2024 - Fani, Tiara; Saptorini, Kriswiharsi Kun (Procedia of Engineering and Life Science, 2024)
Length of hospital stay is an essential indicator of the quality of inpatient hospital services, including in RSD KRMT Wongsonegoro as a Type B hospital in Semarang City. There were various factors related to the length of hospital stay. Therefore, the study objective was to determine the factors associated with the length of stay of inpatients at RSD KRMT Wongsonegoro Semarang. The cross-sectional study distributed a questionnaire to 122 inpatients in RSD KRMT Wongsonegoro from January to February 2024. The variables in this study were patient characteristics, self-rated health status (physical and mental), and hospital stay. The data analysis used descriptive and inferential statistics with comparative tests to determine the study objective. The results showed that the average length of hospital stay among the respondents was five days. The majority of respondents in this study were female patients (55.7%), junior high school (36.9%) and high school graduates (31.1%), and aged >45 years or older (63.9%). The results of the comparison test showed that gender (p-value: 0.987), education (p-value: 0.278), and age (p-value: 0.425) were not associated with the number of patient care days. Based on the comparison test, self-rated physical health (p-value: 0.034) and self-rated mental health (p-value: 0.016) were significantly associated with the number of hospital days. In general, patients who perceived poor physical and psychological health had longer hospital stays than patients who perceived better physical and mental health. Therefore, hospitals need to assess patients' perceived physical and mental health status to improve inpatient services.